ASSESSMENT OF THE INFLUENCE OF ELECTRONIC SCHOOL OF REPRODUCTIVE HEALTH ON THE STATE OF REPRODUCTIVE HEALTH OF ADOLESCENT GIRLS IN THE NOVOSIBIRSK REGION - Лукашева, Ольга Владимировна; Макаров, Константин Юрьевич; Борцов, Виктор Анатольевич; Кихтенко, Николай Андреевич (Mother and Baby in Kuzbass, 2023)
Objective. Тo assess the impact of an electronic reproductive health school on reproductive health indicators and reproductive behavior characteristics of teenage girls in the Novosibirsk region. Results. The characteristics of the control and observation groups upon re-application did not differ from each other. In the observation group, after using information from the electronic school of reproductive health, compared with the control group, there is a tendency towards an increase in the age of sexual debut, and a decrease in the number of teenage girls smoking. Significant statistical differences were revealed in the number of sexual partners: 2.16±0.37 in the control group versus 1.06±0.04 in the observation group upon re-treatment (p<0.001). There were significant differences in adherence to contraception among patients in the observation group during a repeat study compared with teenage girls in the control group. When characterizing the established diagnoses, a significant predominance of inflammatory diseases of the pelvic organs and external genital organs and non-inflammatory diseases was obtained in the control group, and a tendency towards an increase in the request for consultation on contraception and monitoring its use in the control group during a repeat study was established. Conclusions. Timely use by adolescents of preventive information on reproductive health and reproductive behavior posted in the electronic school of reproductive health makes it possible to influence modifiable risk factors for the development of gynecological diseases, helping to preserve the reproductive health of teenage girls.